New Geographical Record of Three-Spine Frogfish, Batrachomoeus Trispinosus (Günther 1861) From the River Rupsa, Bangladesh (Bangladesh Journal of Zoology, 2020)
Abstract Not AvailableBangladesh J. Zool. 48(1): 197-202, 2020